2017
DOI: 10.1177/1352458517703802
|View full text |Cite
|
Sign up to set email alerts
|

Pilot trial of intravenous autologous culture-expanded mesenchymal stem cell transplantation in multiple sclerosis

Abstract: Autologous MSC transplantation in MS appears feasible, safe, and well tolerated. Future trials to assess efficacy more definitively are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 31 publications
2
89
0
Order By: Relevance
“…Nevertheless, an interesting finding was that the highest secretion of IL‐6, IL‐8, and VEGF was detected in MSC‐CM of patients with the lowest number of WM lesions at baseline. As MS8 had the lowest number of lesions and his MSCs expressed the highest amount of the top analytes, he was followed by MS4 who had 60 lesions and expressed the 2nd highest amount. While this correlation was not reflected in the efficacy of treatment in this study, it would be valuable to investigate the biological and therapeutic properties of the MS‐MSCs compared to control individuals and the effect of disease severity in terms of loss of white matter on MSCs and CM‐MSCs content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, an interesting finding was that the highest secretion of IL‐6, IL‐8, and VEGF was detected in MSC‐CM of patients with the lowest number of WM lesions at baseline. As MS8 had the lowest number of lesions and his MSCs expressed the highest amount of the top analytes, he was followed by MS4 who had 60 lesions and expressed the 2nd highest amount. While this correlation was not reflected in the efficacy of treatment in this study, it would be valuable to investigate the biological and therapeutic properties of the MS‐MSCs compared to control individuals and the effect of disease severity in terms of loss of white matter on MSCs and CM‐MSCs content.…”
Section: Discussionmentioning
confidence: 99%
“…In previous clinical studies, the optimal route of stem cell injection, frequency, and number of cells injected has varied and is yet to be determined . In a preclinical study, direct intraventricular MSCs injection has been reported to be more effective in the EAE model compared to the intravenous route .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these studies, 3 were excluded due to less than 5 cases, 3 due to lack of full texts, 5 due to being review and conference articles, and 5 due to relevant data not being extractable. Finally, in this meta-analysis, 9 studies [10][11][12][13][14][15][16][17][18] on aMSCs for the treatment of MS were analyzed which included 133 transplanted patients (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, more than ten publications used expanded to treat some diseases in both local injection and infusion in Pubmed [1][2][3][4][5][6][7][8][9][10]. All publications showed expanded MSC transplantation was safe.…”
Section: Dear Editor-in-chiefmentioning
confidence: 99%